Administration of Pharmaceutical Agents Prior to Testicular Sperm Extraction Procedures: A Meaningful or Meaningless Approach? - Çayan, Selahittin; Yaman, Onder (Current Pharmaceutical Design, 2021)
Background: To date, no randomized and controlled study has demonstrated the effect of adjuvant medical therapy on testicular sperm production before the sperm retrieval procedures in men with non-obstructive azoospermia (NOA). Objectives: To present the available data on the administration of pharmaceutical agents prior to testicular sperm extraction (TESE) procedures in order to obtain better sperm retrieval results in men with NOA. Methods and Results: Various pharmaceutical agents were used empirically to induce spermatogenesis in the treatment of NOA. The rationale for adjuvant hormonal treatment has been to increase intratesticular testosterone levels with different dosages of gonadotropins, anti-estrogen agents, or aromatase inhibitors. Conclusion: Based on the published studies, in the presence of a normal range of peripheral serum total testosterone levels, no medical treatment is advised, and TESE procedures should be performed directly in men with NOA. Further well-designed and randomized, placebo-controlled trials are needed to support the potential benefit of pretreatment prior to TESE procedures.
Keywords: Azoospermia